A conductive MOFs flexible room temperature gas sensor and its preparation method and application

By using VMQ and CB composite materials as flexible substrates and spraying conductive MOFs materials, a conductive MOFs flexible room temperature gas sensor was prepared, which solved the problem of insufficient response speed and stability of ammonia gas detection in the prior art, and achieved the goal of placing a conductive MOFs at room temperature. Fast and stable detection of ammonia.

CN115144442BActive Publication Date: 2025-02-18DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210639180.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-07
Publication Date
2025-02-18
Estimated Expiration
2042-06-07

AI Technical Summary

Technical Problem

The existing flexible gas sensors have insufficient response speed and stability to ammonia detection at room temperature, and few researches have been conducted on conductive polymer flexible substrates.

Method used

A conductive MOFs flexible room temperature gas sensor was prepared by using methylvinyl silicone rubber (VMQ) and carbon black (CB) composite material as a flexible substrate, and the surface was sprayed with conductive MOFs material.

Benefits of technology

It realizes rapid and stable detection of ammonia at room temperature, has good repeatability and stability, is low in cost and is easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115144442B_ABST
    Figure CN115144442B_ABST
Patent Text Reader

Abstract

The present invention discloses a conductive MOFs flexible room temperature gas sensor and a preparation method and application thereof, belonging to the technical field of flexible sensors. The present invention first prepares a composite material of methyl vinyl silicone rubber and carbon black, and then sprays a conductive MOFs sensing material on the surface of the composite material to prepare a conductive MOFs flexible room temperature gas sensor. The present invention saves the cost of depositing electronic circuits on the substrate surface, avoids complex gas-sensitive element preparation processes, and has the advantages of low cost and simple operation; the flexible room temperature gas sensor prepared by the present invention has good repeatability and stability, and can be used for ammonia monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible sensors, and in particular relates to a conductive MOFs flexible room temperature gas sensor, a preparation method and application thereof in ammonia detection at room temperature. Background Art

[0002] Metal organic frameworks (MOFs) have been widely used in gas adsorption, gas storage, gas separation, drug release and catalysis due to their high specific surface area, structural and functional diversity, and high active site density. Compared with other chemical gas sensitive materials, the ultra-high porosity and framework adjustability of MOFs materials have attracted much attention from researchers, providing a new idea for realizing gas room temperature sensing.

[0003] For flexible gas sensors, the sensing layer monitors the resistance change of the gas sensing signal, and the flexible substrate mainly plays a supporting role in bearing bending deformation. Currently, most of the flexible substrates used by researchers are made of paper, textiles, polymers and other materials, but less attention has been paid to conductive polymer flexible substrates.

[0004] Vinyl methyl silicone rubber (VMQ) has excellent heat resistance, low-temperature elasticity and excellent oxidation resistance. It also has high gas permeability and certain gas permeability selectivity. VMQ has the problem of non-conductivity at room temperature. There is no report on the use of VMQ and MOFs to prepare conductive MOFs flexible sensors. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a conductive MOFs flexible room temperature gas sensor for simply, accurately and quickly detecting ammonia, and a preparation method and application thereof. First, a composite material of methyl vinyl silicone rubber (VMQ) and carbon black (CB) is prepared, and then a conductive MOFs sensing material is sprayed on the surface of the material to prepare a conductive MOFs flexible sensor. The series of flexible sensors prepared by the present invention have good repeatability and stability, and can be used for ammonia monitoring.

[0006] The object of the present invention is to achieve the following:

[0007] The present invention provides a method for preparing a conductive MOFs flexible room temperature gas sensor, which mainly comprises the following steps:

[0008] (1) adding silicone rubber to an internal mixer, mixing for 1 to 10 minutes, adding dried carbon black and silane coupling agent, mixing for 1 to 10 minutes, adding a crosslinking agent, mixing for 1 to 10 minutes, and thinning the obtained material on an open mixer for 1 to 20 times. Putting the obtained sample into a mold, and vulcanizing it on a flat plate vulcanizer for 1 to 10 minutes to obtain a conductive flexible substrate with a thickness of 0.2 to 2 mm;

[0009] (2) Spraying a suspension of MOFs material on the surface of the conductive flexible substrate prepared in step (1), and drying in a vacuum drying oven to obtain a conductive MOFs flexible room temperature gas sensor.

[0010] Furthermore, the silicone rubber described in step (1) includes methyl vinyl silicone rubber, ethyl silicone rubber, dimethyl silicone rubber and methyl phenyl vinyl silicone rubber.

[0011] Furthermore, in step (1), the mass percentage of carbon black to silicone rubber is 0.01:100 to 5:100, and the banburying temperature is 50-80°C.

[0012] Furthermore, in step (1), the silane coupling agent is KH540, and the mass percentage of the silane coupling agent to the silicone rubber is 0.5:100 to 2:100.

[0013] Furthermore, in step (1), the crosslinking agent is 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the mass percentage of the crosslinking agent to the silicone rubber is 0.5:100 to 2:100.

[0014] Furthermore, in step (1), the vulcanization temperature is 120-200° C., and the vulcanization pressure is 5-15 MPa.

[0015] Furthermore, in step (1), the mold is a square mold with a side length of 5-20 cm and a thickness of 0.2-2 mm.

[0016] Furthermore, in step (2), the MOFs material is Cu3(HHTP)2, Zn3(HHTP)2 or Ni3(HHTP)2 with hexahydroxytriphenylene (HHTP) as a ligand, and the concentration of the MOFs material in the suspension is 1 to 10 mg / mL.

[0017] Furthermore, the preparation method of Cu3(HHTP)2 includes the following steps: dissolving hexahydroxytriphenylene hydrate and copper salt in deionized water, followed by ultrasonic treatment, and then reacting at 60-100°C for 5-24 hours, collecting the precipitate, and washing it with deionized water and acetone for 1-10 times in sequence, and the obtained sample is dried.

[0018] Furthermore, the preparation method of Zn3(HHTP)2 includes the following steps: dissolving hexahydroxytriphenylene hydrate and zinc salt in deionized water, followed by ultrasonic treatment, and then reacting at 60-100°C for 5-24 hours, collecting the precipitate, and washing it with deionized water and acetone for 1-10 times in sequence, and the obtained sample is dried.

[0019] Furthermore, the preparation method of Ni3(HHTP)2 includes the following steps: dissolving hexahydroxytriphenylene hydrate and nickel salt in deionized water, followed by ultrasonic treatment, and then reacting at 60-100°C for 5-24 hours, collecting the precipitate, and washing it with deionized water and acetone for 1-10 times in sequence, and the obtained sample is dried.

[0020] Furthermore, in step (2), the amount of MOFs material sprayed on the surface of the conductive flexible substrate is 0.5-1.5 mg / cm 2 .

[0021] Another aspect of the present invention provides a conductive MOFs flexible room temperature gas sensor prepared by the above preparation method.

[0022] The present invention also provides application of the conductive MOFs flexible room temperature gas sensor in detecting ammonia at room temperature.

[0023] Furthermore, the conductive MOFs flexible room temperature gas sensor has a high response value and good cycle stability to NH3. Within a response time of 5 minutes, a stable response value of 9.4% can be achieved, and there is a good linear relationship between concentration and response value.

[0024] The beneficial effects of the present invention compared with the prior art are as follows:

[0025] 1. The present invention first prepares a flexible substrate from the VMQ / CB composite material by a mechanical blending method, and then loads the conductive MOFs material on the surface of the flexible substrate by a spraying method. The prepared Cu3(HHTP)2 / VMQ / CB flexible sensor can save the cost of depositing electronic circuits on the substrate surface, avoid complex gas-sensitive element preparation processes, and has the advantages of low cost and easy operation.

[0026] 2. The present invention utilizes the gas-sensitive property of conductive MOFs material at room temperature as the sensing layer material of the flexible sensor, so that it has a stable response value (9.4%) to 500ppm NH3 gas in a relatively short time (5min) at room temperature; within the bending deformation range of -15° to 15°, the response value has good repeatability and stability, and even under larger deformation, it has an observable response signal. The flexible sensor of the present invention using conductive MOFs material as the sensing layer and conductive polymer as the flexible substrate has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0028] Figure 1The gas-sensing performance test of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3, wherein (a) is the dynamic cycle response curve of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3, (b) is the dynamic response curve of Cu3(HHTP)2 / VMQ / 30CB to 100-500ppm NH3, and (c) is the fitting straight line between the response value and the NH3 gas concentration;

[0029] Figure 2 This is the dynamic response curve of Cu3(HHTP)2 / VMQ / 20CB to 500ppm NH3;

[0030] Figure 3 The dynamic cycle response curve of Ni3(HHTP)2 / VMQ / 30CB to 500ppm NH3;

[0031] Figure 4 The gas sensing performance test of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3 under bending deformation, wherein (a) is the dynamic response curve of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3 under different bending deformations, and (b) is the dynamic response curve of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3 after 100 repeated bending cycles at a bending angle of -15° to 15°;

[0032] Figure 5 Dynamic response curves of Cu3(HHTP)2 / VMQ / 30CB under (a) 20% stretching and (b) 180° twisting deformation. DETAILED DESCRIPTION

[0033] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0034] Example 1

[0035] The preparation of Cu3(HHTP)2 in this embodiment is obtained by the preparation method of New Porous Crystals of Extended Metal-Catecholates, Chem. Mater. 2012, 24, 18, 3511-3513. The specific preparation process includes: adding 28.5 mg of hexahydroxytriphenylene hydrate and 32 mg of copper trifluoroacetylacetonate into a 20 mL glass bottle, and dissolving them in 4 mL of deionized water, then ultrasonicating for 15 min to obtain a dark blue solution, placing the bottle in an 85°C oven, and reacting for 24 hours. After the reaction is completed, the precipitate is collected by centrifugation, and washed with deionized water and acetone for multiple times, and the washed sample is placed in a 60°C vacuum drying oven for 12 hours to obtain the final product Cu3(HHTP)2.

[0036] Add 100g of methyl vinyl silicone rubber (VMQ) into an internal mixer at a mixing temperature of 60°C. After mixing for 2 minutes, slowly add 30mg of carbon black (CB), then add 1phr of silane coupling agent KH540 and mix for 5 minutes. Add 1phr of crosslinking agent 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane and mix for 3 minutes before taking out. In order to fully mix the materials, the materials were thinned on an open mill for 10 times; the obtained sample was placed in a mold and vulcanized at 160°C and 10 MPa for 8 minutes through a flat vulcanizer to obtain a film with a thickness of 0.5 mm; the prepared 0.5 mm VMQ / 30CB film was divided into small rectangles with a length of 25 mm and a width of 6 mm, and the Cu3(HHTP)2 powder was fully ground, acetone was added and stirred to prepare an acetone suspension with a concentration of 2 mg / mL, and the Cu3(HHTP)2 acetone suspension was evenly sprayed on the prepared VMQ / 30CB, sprayed 10-15 times, and the cumulative spraying amount was 1 mg / cm 2 .

[0037] The cyclic dynamic response curve of Cu3(HHTP)2 / VMQ / 30CB prepared in Example 1 to 500ppm NH3 is as follows: Figure 1 As shown in (a), the dynamic response curve of the sensor to 100-500ppm NH3 is as follows Figure 1 As shown in (b), the fitting straight line between concentration and response value is Figure 1 As shown in (c), it can be seen that the Cu3(HHTP)2 / VMQ / 30CB prepared in Example 1 has a high response value and good cycle stability to 500ppm NH3. Within a response time of 5 minutes, a stable response value of 9.4% can be achieved. There is a good linear relationship between the concentration and the response value, and the correlation coefficient R 2 is 0.995.

[0038] Example 2

[0039] Add 100g VMQ into the internal mixer at 60℃. After 2min of internal mixing, slowly add 20mg CB, then add 1phr silane coupling agent KH540, knead for 5min, add 1phr crosslinking agent 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, knead for 3min and then take out; in order to fully mix the materials, pass the materials on the open mill 10 times; put the obtained sample in the mold, and vulcanize it at 160℃ and 10MPa pressure for 8min through the flat plate vulcanizer to obtain a film with a thickness of 0.5mm; divide the prepared 0.5mm VMQ / 20CB film into small rectangles with a length of 25mm and a width of 6mm, and grind the Cu3(HHTP)2 powder thoroughly, add acetone and stir thoroughly to prepare an acetone suspension with a concentration of 2mg / mL, and spray the Cu3(HHTP)2 acetone suspension evenly on the prepared VMQ / 20CB, spray 10-15 times, and the spraying amount is 1mg / cm 2 .

[0040] The dynamic response curve of Cu3(HHTP)2 / VMQ / 20CB prepared in Example 2 to 500ppm NH3 is as follows: Figure 2 As shown, it can be seen that the Cu3(HHTP)2 / VMQ / 20CB prepared in Example 2 has a higher response value to 500ppm NH3, and can reach a stable response value of 13.0% within a response time of 5 minutes.

[0041] Example 3

[0042] The preparation of Ni3(HHTP)2 in this embodiment is obtained by the preparation method of New Porous Crystals of Extended Metal-Catecholates, Chem. Mater. 2012, 24, 18, 3511-3513. The specific preparation process includes: adding 35 mg of hexahydroxytriphenylene hydrate and 50 mg of nickel acetate into a 20 mL glass bottle, and dissolving them in 6 mL of deionized water, then ultrasonicating for 15 min to obtain a dark blue solution, placing the bottle in an 85°C oven, and reacting for 12 hours. After the reaction is completed, the precipitate is collected by centrifugation, and washed with deionized water and acetone for multiple times, and the washed sample is placed in a 60°C vacuum drying oven for 12 hours to obtain the final product Ni3(HHTP)2.

[0043] Add 100g VMQ into the internal mixer at 60℃. After 2min of internal mixing, slowly add 30mg CB, then add 1phr silane coupling agent KH540, knead for 5min, add 1phr crosslinking agent 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, knead for 3min and take out. In order to fully mix the materials, pass the materials on the open mill 10 times, put the obtained sample in the mold, and vulcanize it at 160℃ and 10MPa pressure for 8min through the flat vulcanizer to obtain a film with a thickness of 0.5mm; divide the prepared 0.5mm VMQ / 30CB film into small rectangles with a length of 25mm and a width of 6mm, and grind the Ni3(HHTP)2 powder thoroughly, add acetone and stir thoroughly to prepare an acetone suspension with a concentration of 2mg / mL; spray the Ni3(HHTP)2 acetone suspension evenly on the prepared VMQ / 30CB, spray 10-15 times, and the spraying amount is 1mg / cm 2 .

[0044] The dynamic cycle response curve of Ni3(HHTP)2 / VMQ / 30CB prepared in Example 3 to 500ppm NH3 is as follows: Figure 3 As shown, it can be seen that the Ni3(HHTP)2 / VMQ / 30CB prepared in Example 3 has a stable response to 500ppm NH3, and can reach a response value of 3.6% within a response time of 5 minutes.

[0045] Example 4

[0046] This example is used to detect the response value of the Cu3(HHTP)2 / VMQ / 30CB sensor prepared in Example 1 to NH3 under bending deformation, test the change in the response value of the sensor to 500ppm NH3 under bending deformations of -30°, -15°, 0°, 15°, and 30°, evaluate the bending deformation range in which Cu3(HHTP)2 / VMQ / 30CB maintains a stable response, and further test the response value of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3 after 100 repeated bendings at a bending angle of -15° to 15° based on the test results.

[0047] The dynamic response curves of the Cu3(HHTP)2 / VMQ / 30CB sensor to 500ppm NH3 under bending deformations of -30°, -15°, 0°, 15°, and 30° are as follows: Figure 4 As shown in (a), after 100 repeated bending cycles with a bending angle of -15° to 15°, the dynamic response curve of the sensor to 500ppm NH3 is shown in Figure 4(c) As shown; it can be seen that the response value of the Cu3(HHTP)2 / VMQ / 30CB prepared in Example 1 is not greatly affected in the case of 15° deformation, whether it is bent upward or downward, and the response value decreases to varying degrees in the case of 30° deformation. The decrease in the response of the sensor bent downward by 30° may be due to the presence of more cracks in the microscopic sensing layer, which leads to an increase in resistance, while the flexible substrate does not participate in the gas response, and this part of the resistance does not increase after the gas is introduced, resulting in a decrease in the overall response. The response of the sensor bent upward by 30° also decreases, which may be due to the increase in the overall resistance of the sensing layer and the flexible substrate due to the larger deformation, and the bending of the sensing layer may lead to a decrease in the desorption rate of the gas on the surface of the material. After 100 repeated bendings at angles ranging from -15° to 15°, the response value of Cu3(HHTP)2 / VMQ / 30CB remained basically unchanged, indicating that Cu3(HHTP)2 / VMQ / 30CB can maintain the stability of its gas-sensing performance within the bending angle range of -15° to 15°, and can also have a certain detectable gas-sensing signal within a slightly larger bending angle.

[0048] Example 5

[0049] This embodiment is used to detect the response value test experiment of Cu3(HHTP)2 / VMQ / 30CB prepared in Example 1 to NH3 under tensile deformation. By testing the change of the sensor response value to 500ppm NH3 of Cu3(HHTP)2 / VMQ / 30CB under 20% tensile deformation or 180° distortion, the response value of Cu3(HHTP)2 / VMQ / 30CB to 500ppm NH3 under larger destructive deformation is tested.

[0050] The dynamic response of Cu3(HHTP)2 / VMQ / 30CB under 20% stretching or 180° twisting deformation is shown in Figure 2. Figure 5 As shown, the Cu3(HHTP)2 / VMQ / 30CB prepared in Example 1 can reach a response value of 2.2% to 500ppm of NH3 within a response time of 5 minutes under a tensile deformation of 20%; and can reach a response value of 1.8% to 500ppm of NH3 within a response time of 5 minutes under a twisting deformation of 180°. It can be seen that the Cu3(HHTP)2 / VMQ / 30CB sensor has certain tensile properties in addition to bending properties. Compared with textile-based and paper-based gas sensors and flexible gas sensors prepared using deposition circuits, the sensor of the present application has greater deformation capacity.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a conductive MOFs flexible room temperature gas sensor, characterized in that: The main steps include: (1) adding silicone rubber to an internal mixer, mixing for 1 to 10 minutes, adding carbon black and silane coupling agent, mixing for 1 to 10 minutes, adding a crosslinking agent, mixing for 1 to 10 minutes, and thinning the obtained material on an open mixer for 1 to 20 times. Putting the obtained sample into a mold, and vulcanizing it on a flat plate vulcanizer for 1 to 10 minutes to obtain a conductive flexible substrate with a thickness of 0.2 to 2 mm; (2) spraying a suspension of MOFs material on the surface of the conductive flexible substrate prepared in step (1), and preparing a conductive MOFs flexible room temperature gas sensor after drying; In step (2), the MOFs material is Cu3(HHTP)2, Zn3(HHTP)2 or Ni3(HHTP)2; The silicone rubber described in step (1) includes methyl vinyl silicone rubber, ethyl silicone rubber, dimethyl silicone rubber and methyl phenyl vinyl silicone rubber; In step (1), the mass percentage of carbon black to silicone rubber is 0.01:100 to 5:100, and the banburying temperature is 50-80° C.; In step (1), the silane coupling agent is KH540, and the mass percentage of the silane coupling agent to the silicone rubber is 0.5:100 to 2:100; In step (1), the crosslinking agent is 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, and the mass percentage of the crosslinking agent to the silicone rubber is 0.5:100 to 2:

100.

2. The preparation method according to claim 1, characterized in that: In step (1), the vulcanization temperature is 120-200° C. and the vulcanization pressure is 5-15 MPa.

3. The preparation method according to any one of claims 1 to 2, characterized in that: The concentration of the MOFs material in the suspension in step (2) is 1 to 10 mg / mL.

4. The preparation method according to claim 3, characterized in that: The amount of MOFs material sprayed on the surface of the conductive flexible substrate in step (2) is 0.5-1.5 mg / cm 2 .

5. A conductive MOFs flexible room temperature gas sensor prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the conductive MOFs flexible room temperature gas sensor according to claim 5 in detecting ammonia at room temperature.